Constructing Evil: U.S. Media Discourse and the Iranian State Murder of Neda Agha-Soltan - Turner, Justin (2012)
On June 20, 2009, one image became not only a symbol of unbridled state violence, but a rallying cry for a movement contesting the disputed election of hardline Iranian President Mahmoud Ahmadinejad. The particular image in question was of Neda Agha-Soltan, a 26 year old woman whose murder was recorded by cellphone camera during a political protest and subsequently posted to social media networks showing a graphic fist-hand account of the savagery of a state crime. Media discourse presented the idea that Neda's murder was committed by the Iranian government unafraid to implore repressive measures to control its population. The question posed in this analysis is how did media discourse frame her murder, and what were the consequences. In studying media discourse surrounding the event, I focused on how Neda's murder was constructed in the New York Times and Washington Post from June 23, 2009 to June 30, 2009. However, this construction was framed through Orientalism, which created a dichotomy between good and bad Muslims. This dichotomy was found to situate the protesters as good Muslims, while portraying President Ahmadinejad and the Iranian government as bad . Within a framing of good' Muslim and bad Muslim, the United States elite media discourse represented an image of the Iranian government as evil, childlike, and violent, while portraying the protesters as innocent, repressed, and seeking protection. Elite discourse would shape the video of Neda Agha Soltan's murder as an instrument that could help justify deploying more military force into the Middle East